2018
DOI: 10.1038/s41598-018-28375-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the key regulatory genes and their Interologs for Turner Syndrome employing network approach

Abstract: Turner Syndrome (TS) is a condition where several genes are affected but the molecular mechanism remains unknown. Identifying the genes that regulate the TS network is one of the main challenges in understanding its aetiology. Here, we studied the regulatory network from manually curated genes reported in the literature and identified essential proteins involved in TS. The power-law distribution analysis showed that TS network carries scale-free hierarchical fractal attributes. This organization of the network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Since ovarian cancer PPI interaction network follows hierarchical scale free nature, the emergence of modules in the network is significant and therefore both these sparsely distributed few leading hubs regulate and modules, which is organize the network. Application of Newmann and Girvan’s standard community finding algorithm, the modular structure and their organization at different levels of organization were established (see Methods) [14, 17, 32]. Applying the present algorithm, the ovarian cancer network is established to be hierarchically organized through five various levels of organization shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since ovarian cancer PPI interaction network follows hierarchical scale free nature, the emergence of modules in the network is significant and therefore both these sparsely distributed few leading hubs regulate and modules, which is organize the network. Application of Newmann and Girvan’s standard community finding algorithm, the modular structure and their organization at different levels of organization were established (see Methods) [14, 17, 32]. Applying the present algorithm, the ovarian cancer network is established to be hierarchically organized through five various levels of organization shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Turner syndrome patients surviving to adulthood are most probably mosaic cases [115] where some cells have two X chromosomes or an X and a Y chromosome. Network analysis found that KDM6A is a key regulator in Turner syndrome [116]. KDM6A is a potential candidate gene for premature ovarian failure in Turner syndrome [117,118] because of its role in fertility and pluripotency (Section 2.3), and may be involved in gonadal dysgenesis [119].…”
Section: Kdm6a In Genetic Conditionsmentioning
confidence: 99%
“…GCN hubs) with biological functions/processes in cells and tissues 25 , 26 . Actually, targeted hub attacks in protein-protein and gene-gene networks have been used to disclose relevant functional genes in health and disease 26 28 . Therefore, GCN hubs are relevant both for network topology and cell functioning.…”
Section: Resultsmentioning
confidence: 99%